2005
DOI: 10.1111/j.1471-0528.2004.00518.x
|View full text |Cite
|
Sign up to set email alerts
|

Tocolysis for repeat external cephalic version in breech presentation at term: a randomised, double‐blinded, placebo‐controlled trial

Abstract: Background External cephalic version (ECV) reduces the incidence of breech presentation at term and caesarean section for non-cephalic births. Tocolytics may improve success rates, but are time consuming, may cause side effects and have not been proven to alter caesarean section rates. The aim of this trial was to determine whether tocolysis should be used if ECV is being re-attempted after a failed attempt. Objective To determine whether tocolysis should be used if ECV is being re-attempted after a failed att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 15 publications
0
23
1
Order By: Relevance
“…Obviously, if an aggressive practice of ECV is undertaken the percentages are likely to be halved, particularly in multiparae. 8,9 However, a cephalic presentation at 28-32 weeks results in a 0.85% risk of abnormal presentation in primiparae, and a 0.68% risk in multiparae by 38 weeks.…”
Section: Discussionmentioning
confidence: 96%
“…Obviously, if an aggressive practice of ECV is undertaken the percentages are likely to be halved, particularly in multiparae. 8,9 However, a cephalic presentation at 28-32 weeks results in a 0.85% risk of abnormal presentation in primiparae, and a 0.68% risk in multiparae by 38 weeks.…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, these agents do not decrease the neonatal mortality and morbidity associated with PTL. Thus, the popularity of these agents as first-line tocolytic agents has decreased 1617. Nevertheless, these agents are recommended as first-line tocolytic agents because of their efficacy 1214…”
Section: Discussionmentioning
confidence: 99%
“…More recent randomised studies confirmed that the administration of ritodrine prior to ECV improved outcome compared to placebo (11), (12). Impey and Pandit, in fact, suggested that atosiban may be a safer alternative compared to ritodrine due to its better side effect profile and as its’ shorter duration of exposure (12).…”
Section: Discussionmentioning
confidence: 99%